Spotted Fever Group Rickettsia Infecting Ticks (Acari: Ixodidae), Yak (Bos grunniens), and Tibetan Sheep (Ovis aries) in the Qinghai–Tibetan Plateau Area, China - He, Yong-Cai; Li, Ji-Xu; Sun, Ya-Li; Kang, Ming; He, Hong-Xuan; Guo, Yun-Hai; Ma, Ping; Wei, Yao-Ping; Li, Rui-Shan; Chen, Wang-Kai; Chen, Zhi-Hong; Li, Jing; et al. (Frontiers in Veterinary Science, 2022)
The Qinghai-Tibet Plateau Area (QTPA) has a complex natural ecosystem, causing a greatly increased risk of spreading various tick-borne diseases including rickettsial infections, which regarded as one of the oldest known vector-borne zoonoses. However, the information of one of its pathogen, Spotted Fever Group Rickettsia (SFG Rickettsia), is limited in tick vectors and animals in this area. Therefore, this study focused on the investigation of SFG Rickettsia in tick vectors, yaks (Bos grunniens) and Tibetan sheep (Ovis aries) in the QTPA. A total of 1000 samples were collected from nine sampling sites, including 425 of yaks, 309 of Tibetan sheep, 266 of ticks. By morphological examination, PCR and sequencing, we confirmed the species of all collected ticks. All tick samples, all yak and Tibetan sheep blood samples were detected based on SFG Rickettsia ompA and sca4 gene. The results showed that all tick samples were identified to be Haemaphysalis qinghaiensis, and the positive rates of SFG Rickettsia were 5.9% (25/425), 0.3% (1/309) and 54.1% (144/266) in yaks, Tibetan sheep and ticks, respectively. All positive samples were sequenced, and BLASTn analysis of the ompA gene sequences of SFG Rickettsia showed that all positive samples from animals and ticks had 99.04–100% identity with yak and horse isolates from Qinghai Province, China. BLASTn analysis of the sca4 gene sequences of SFG Rickettsia showed that all positive samples had 97.60–98.72% identity with tick isolates from Ukraine. In addition, the phylogenetic analysis showed that all the SFG Rickettsia ompA and sca4 sequences obtained from this study belong to the same clade as Rickettsia raoultii isolated from livestock and ticks from China and other countries. Molecularly, This study detected and characterized SFG Rickettsia both in the tick vectors and animals, suggesting that the relationship between SFG Rickettsia, tick species and animal hosts should be explored to understand their interrelationships, which providing a theoretical basis for preventing control of this pathogen.